Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1001/jamasurg.2017.3422
|View full text |Cite
|
Sign up to set email alerts
|

Oncologic Safety of Prophylactic Nipple-Sparing Mastectomy in a Population With BRCA Mutations

Abstract: Nipple-sparing mastectomies are highly preventive against breast cancer in a BRCA population. Although the follow-up remains relatively short, NSM should be offered as a breast cancer risk-reducing strategy to appropriate patients with BRCA mutations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
102
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(111 citation statements)
references
References 33 publications
3
102
0
1
Order By: Relevance
“…However, in selected cases (figure 4), if the surgical strategy is discussed and is in accordance with patient’s wishes (also considering the uncontrolled fear, which is frequently observed in these situations), a prophylactic bilateral nipple-sparing mastectomy (PNSM) could be performed as defined for BRCA mutation carriers 89…”
Section: Prophylactic Surgerymentioning
confidence: 99%
“…However, in selected cases (figure 4), if the surgical strategy is discussed and is in accordance with patient’s wishes (also considering the uncontrolled fear, which is frequently observed in these situations), a prophylactic bilateral nipple-sparing mastectomy (PNSM) could be performed as defined for BRCA mutation carriers 89…”
Section: Prophylactic Surgerymentioning
confidence: 99%
“…2,29,30 Oncologic safety of NSM has also been demonstrated in the population with BRCA mutations as well. 31 Our study demonstrates that in addition to widely accepted level of oncologic safety, NSM provides patients with higher levels of sexual well-being while maintaining comparable levels of satisfaction with the breasts, as well as physical and psychosocial well-being.…”
Section: Discussionmentioning
confidence: 54%
“…Oncologic safety has been demonstrated in those undergoing NSM as studies have shown local recurrence rate ranging from 2.3‐8.2%, comparable to the rates in conventional mastectomy patients . Oncologic safety of NSM has also been demonstrated in the population with BRCA mutations as well …”
Section: Discussionmentioning
confidence: 94%
“…Nipple‐sparing (NSM) and skin‐sparing (SSM) mastectomies require a less extensive reconstruction and often a better cosmetic result. Since the PROSE study in 2004, a piece of mounting evidence demonstrates that NSM, as well as SSM, may be effective forms of surgical prophylaxis in BRCA carriers . In a recent retrospective study, patients with BRCA who underwent prophylactic NSM at nine institutions from 1968‐2013 were reviewed .…”
Section: Hereditary Breast and Ovarian Cancer Syndromementioning
confidence: 99%